Vibration therapy versus standard treatment for tennis elbow: A randomized controlled study. (14th August 2018) - Furness, Nicholas Duncan; Phillips, Alistair; Gallacher, Sian; Beazley, James Charles Sherard; Evans, Jonathan Peter; Toms, Andrew David; Thomas, William; Smith, Christopher David
Aim: To determine whether a mechanical, high-frequency vibration device (Tenease ™ ) can improve pain and function for the treatment of tennis elbow (TE), compared with standard treatment. Methods: Adults presenting to an elbow clinic with a clinical diagnosis of TE were randomized to standard treatment with physiotherapy, activity modification and analgesia or standard treatment plus Tenease therapy. Tenease therapy consisted of a 6-week period of treatment using the Tenease device with three 10-min episodes each day. The primary outcome measure was the quick Disabilities of the Arm, Shoulder and Hand score at 6 months, with scores also taken at 6 weeks. Secondary outcome measures were the Patient Rated Tennis Elbow Evaluation Score and EuroQol 5-Dimension Visual Analogue Scale at the same time points. Results: Fifty-four patients were recruited into the study. Following randomization and initial dropout, 18 patients were included in the standard group and 27 in the Tenease group. Both groups reported improvements in primary outcome measure scores. The control group had a mean score of 44.3 (standard deviation (SD) = 18.8) at baseline, which dropped to 31.2 (SD = 17.2) at 6 months ( p = 0.002). The Tenease group had a mean score of 43.2 (SD = 22.7) at baseline, which dropped to 23.4 (SD = 15.0) at 6 months ( p = 0.064). Similar improvements were seen in secondary outcome measures with none reaching statistical significance. There were no statistically significant differences seen between the primary outcome scores at 6 weeks ( p = 0.9) or 6 months ( p = 0.5). No complications were noted in either group. Conclusions: Vibration therapy did not result in any statistically significant improvement in functional outcome scores compared to standard treatment for TE. It is important to note that this was a relatively small cohort and a high dropout rate was observed.